Informator / "Solidarność" Region Środkowo-Wschodni . no. 155, 1988 - "Solidarność" Region Środkowo-Wschodni ([s.n.], 1988)
Creation and circulation: Publication contains listing of titles of Polish underground press, mostly from Środkowo-Wschodni region